A Comparative Study of Approved Drugs for SARS-CoV-2 by Molecular Docking - Achal Mishra; Radhika Waghela (Journal of Molecular Docking, 2021)
SARS-CoV-2, a new type of Coronavirus, has affected more millions of people worldwide. From the spread of this infection, many studies related to this virus and drug designing for the treatment have been started. Most of the studies target the SARS-CoV-2 main protease, spike protein of SASR-CoV-2, and some are targeting the human furin protease. In the current work, we chose the clinically used drug molecules remdesivir, favipiravir, lopinavir, hydroxychloroquine, and chloroquine onto the target protein SARS-CoV-2 main protease. Docking studies were performed using Arguslab, while Discovery Studio collected 2D and 3D pose views with the crystal structure of COVID-19 main protease in complex with an inhibitor N3 with PDB ID 6LU7. Computational studies reveal that all ligands provided good binding affinities towards the target protein. Among all the chosen drugs, lopinavir showed the highest docking score of -11.75 kcal/mol. The results from this molecular docking study encourage the use of lopinavir as the first-line treatment drug due to its highest binding affinity.